2012
DOI: 10.1186/1752-1947-6-43
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus co-infection in a patient with dengue fever presenting with post-infectious cerebellitis: a case report

Abstract: IntroductionPost-infectious cerebellitis is an acute form of inflammatory encephalitis mainly limited to the cerebellum. It is commonly found in children, especially after viral infections such as Epstein-Barr virus. Post-infectious cerebellitis presents with acute onset dysarthria and ataxia. To the best of our knowledge, this is the first case report of post-infectious cerebellitis in a patient with both dengue and Epstein-Barr viral infection confirmed on serology.Case presentationA 43-year-old Sri Lankan S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…We identified only isolated case reports of patients with dengue fever presenting with symptoms of cerebellitis ( 7 ) . Cerebellar involvement in dengue patients has been thought to be part of a postinfectious immune-mediated process ( 27 ) . However, there have been reports of cerebellar infection in patients with dengue, in whom pathological studies have revealed the presence of viral antigen in the cerebellar cells ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…We identified only isolated case reports of patients with dengue fever presenting with symptoms of cerebellitis ( 7 ) . Cerebellar involvement in dengue patients has been thought to be part of a postinfectious immune-mediated process ( 27 ) . However, there have been reports of cerebellar infection in patients with dengue, in whom pathological studies have revealed the presence of viral antigen in the cerebellar cells ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies on the aetiology of meningoencephalitis in Sri Lanka have been reported [Peiris et al, ; Peiris et al, ; Gunasekera et al, ; Karunarathne et al, ; Mori et al, ] due to limited diagnostic testing capabilities. Routine diagnostic services are available only for JEV by ELISA‐based IgM antibody detection in the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from India report similar findings4 5 and highlight some rare manifestations including mononeuropathies,1 acute disseminated encephalomyelitis,1 6 Guillain–Barré syndrome,1 acute viral myositis1 and hypokalaemic quadriparesis 7. Previously reported cases from Sri Lanka included a case of 6th nerve palsy8 and one of cerebellar syndrome due to dengue and Epstein–Barr virus coinfection 9. Dengue rarely leads to a cerebellar syndrome.…”
Section: Discussionmentioning
confidence: 60%